Comparative Analysis of Immunochemical Methods Applied for Studies of Pathogenic Burkholderia Antigens - I. I. Korsakova (Проблемы особо опасных инфекций, 2012)
Studied are immunochemical properties of antigen preparations, the spectrum and molar masses of the components contained. Demonstrated is the significance of vertical SDS-polyacrylamide gel electrophoresis, immunodiffusion test, immunoelectrophoresis assay, rocket immunoelectrophoresis with specific sera for identification and differentiation of Burkholderia. Rocket immunoelectrophoresis should be viewed as the most informative method which allows for differentiation between pathogenic and non-pathogenic for humans Burkholderia under usual terms.